The criticism of didactic poetry : essays on Lucretius, Virgil, and Ovid - Dalzell, Alexander (Robson classical lectures., 1996)
Dalzell presents three of the major didactic poems in the classical canon: the De rerum natura of Lucretius, the Georgics of Virgil, and the Ars amatoria of Ovid, considering what tools are available for their understanding.